2017
DOI: 10.1111/add.13898
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a temporary class drug order on ethylphenidate‐related infections among people who inject drugs in Lothian, Scotland: an interrupted time–series analysis

Abstract: The UK government's 2015 temporary class drug order on ethylphenidate was effective in reducing infections among people who inject drugs during an outbreak situation in Lothian, Scotland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Firstly, the inclusion of an NPS specific question in the survey in 2015-16 may partly explain the increase in NPS use we observed. However, numerous other sources (Griffith et al, 2016;Lafferty et al, 2016;Yeung et al, 2017;Pettie et al, 2018) have also confirmed a rise in NPS injecting in Lothian at this time therefore we are reassured that the increase we observed in our data is reflective of the actual trend occurring at the time.…”
Section: { Page \* Mergeformat }supporting
confidence: 78%
See 3 more Smart Citations
“…Firstly, the inclusion of an NPS specific question in the survey in 2015-16 may partly explain the increase in NPS use we observed. However, numerous other sources (Griffith et al, 2016;Lafferty et al, 2016;Yeung et al, 2017;Pettie et al, 2018) have also confirmed a rise in NPS injecting in Lothian at this time therefore we are reassured that the increase we observed in our data is reflective of the actual trend occurring at the time.…”
Section: { Page \* Mergeformat }supporting
confidence: 78%
“…This includes adapting content of existing interventions, enhancing their delivery in settings where NPS users are likely to be accessible, and ensuring staff (and peers where appropriate) are adequately trained to deliver them. Legislative changes to specific NPS have been effective at reducing harms in the past within an outbreak situation (Yeung et al, 2017). It remains to be seen whether more universal approaches, such as the recent UK Psychoactive Substances Act, will have a similar positive effect.…”
Section: { Page \* Mergeformat }mentioning
confidence: 99%
See 2 more Smart Citations
“…Although these quantitative studies highlight the associations between risk or protective factors and SSTI, qualitative studies are needed to help understand the many explanations within the PWIDs' within NHS Greater Glasgow and Clyde Health Board. These research sites were chosen as these Health Boards have sizeable injecting populations and unpublished survey data indicated the proportion of PWID reporting an SSTI in the past year was 36% and 27% respectively (unpublished University of the West of (Yeung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%